Existentialism is a humanism - Sartre, Jean-Paul; Macomber, Carol; Cohen-Solal, Annie; Kulka, John (London Yale University press, 2007)
It was to correct common misconceptions about his thought that Sartre accepted an invitation to speak on October 29, 1945, at the Club Maintenant in Paris. The unstated objective of his lecture ("Existentialism Is a Humanism") was to expound his philosophy as a form of "existentialism," a term much bandied about at the time. Sartre asserted that existentialism was essentially a doctrine for philosophers, though, ironically, he was about to make it accessible to a general audience. The published text of his lecture quickly became one of the bibles of existentialism and made Sartre an international celebrity.